2019
DOI: 10.1007/s00005-019-00555-4
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1 Genotype in Periodontitis

Abstract: This paper presents the current knowledge concerning the role of polymorphisms of IL1A and IL1B genes in periodontitis. Attention has been paid to the role of IL-1 in the pathogenesis of the disease, and to the significance of a genetic test, investigating the presence of composite two polymorphisms of IL-1 gene, as a risk factor for severe periodontitis. The significance of this test for prevention of periodontitis and its therapy has been discussed. IL-1 polymorphisms have been presented and described accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 42 publications
(97 reference statements)
0
10
1
Order By: Relevance
“…The prevalence of periodontitis was significantly associated with the salivary microbiome, but not with SNPs. Some studies showed the association between SNPs and periodontitis [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ], but few studies assessed the relationships among polymorphisms, the microbiome, and periodontitis simultaneously. The results showed that the microbiome, rather than SNPs, affected the prevalence of periodontitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of periodontitis was significantly associated with the salivary microbiome, but not with SNPs. Some studies showed the association between SNPs and periodontitis [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ], but few studies assessed the relationships among polymorphisms, the microbiome, and periodontitis simultaneously. The results showed that the microbiome, rather than SNPs, affected the prevalence of periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…After genotype imputation, variants with an R 2 < 0.3 were excluded, resulting in 12,617,547 variants. Of the SNPs that passed quality control, 51 SNPs related to periodontitis were identified [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…They participate in systemic inflammation and play vital roles in innate and adaptive immunity. Previous studies had indicated that IL gene SNPs associate with the development of both bacteria-and virus-related inflammatory disorders, such as sepsis [9,10], periodontitis [11,12], hepatitis B [13], and C [14] virus infections. However, current studies were still limited regarding the potential associations between IL gene SNPs and the risks of developing PTOM, especially in Chinese population.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to our results, when Belstrøm et al used microarrays to examine the oral microbiomes of 292 Danish individuals with low levels of dental caries and periodontitis, they found that diet, BMI, age, and sex did not significantly affect microbial abundance, though socioeconomic status affected the oral microbiome profiles [ 42 ]. Other possible factors could explain the differences observed in our study, including genetic variations, social factors, chronology of tooth eruption, and hormonal differences, which could affect the composition of the plaque microbiomes [ 14 , 43 ].…”
Section: Discussionmentioning
confidence: 99%